Early beans (Phaseolus vulgaris L. and P. Lunatus) L. domesticated for their aesthetic value? - Debouck, Daniel G. (1989)
Some historical aspects and 2 possible reasons for the domestication of Phaseolus vulgaris and P. lunatus are considered, namely, that (1) bean domestication occurred at least 8000 yr ago in the southern Peruvian Andes, as a food plant, or that (2) beans were domesticated for different reasons and then used as food plants. Some kind of aesthetical selection accounts for the diversity of many crops in the New World, which ended when bean domestication started, resulting in undesirable consequences such as the relatively high levels of cyanogenic glucosides in some P. lunatus cv. (CIAT)